Laser-ablated titania nanoparticles for aqueous processed hybrid solar cells. Issue 7 (27th January 2015) - Körstgens, V.; Pröller, S.; Buchmann, T.; Moseguí González, D.; Song, L.; Yao, Y.; Wang, W.; Werhahn, J.; Santoro, G.; Roth, S. V.; Iglev, H.; Kienberger, R.; et al.
Abstract : The active layer of hybrid solar cells is realized with titanium dioxide nanoparticles by laser ablation in liquid and a water-soluble polythiophene. Abstract : Titania nanoparticles are produced by laser ablation in liquid in order to initiate functionalization of titania with the polymer for the active layer. By combining these titania nanoparticles and water-soluble poly[3-(potassium-6-hexanoate)thiophene-2, 5-diyl] (P3P6T) hybrid solar cells are realized.